Oniryzm jako strategia kreowania przestrzeni niesamowitej w najnowszej polskiej literaturze weird fiction - Poniatyszyn, Kajetan (Przestrzenie Teorii, 2025)
The main aim of this article is to describe one of the strategies of creating uncanny space in contemporary Polish weird fiction literature. Initially, the text focuses on general information about oneirismin literature, as well as the combining of the real and supernatural order in the context of Manuel Aguirre’s two-space model, constitutive for space in weird fiction. Subsequently, the concept of oneirismis linked to the Freudian uncanny and the work of Bruno Schulz, which is extremely important for the literature under analysis. The second part of the article is devoted to the analysis of short stories: Horror vacui by Robert Zawadzki, Wezwanie by Wojciech Gunia and Król karaluchów by Ian Giedrojć.